Analisis Hubungan Kerja Antara Satreskrim dan Satintelkam Polri dalam Pengungkapan Tindak Pidana di Polres Pohuwato - Nurdiana Lestari; Rustam Hs. Akili; Nurmik K. Martam (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The working relationship/coordination between Satreskrim and Satintelkam in uncovering criminal offences at Pohuwato Police Station has not gone well. Field Guidelines (Juklap) of the National Police Chief number 189 of 1993 regulates the Relationship between the Working Procedures of the Resersepol Function (Police Detection) and the Intelpampol Function (Police Intelligence and Security) in the context of integrated crime handling, which should be the basis for implementing working relationships, not implemented. The level of coordination and collaboration between Satreskrim and Satintelkam at Polres Pohuwato shows an unstable and often situational cooperation. Collaboration is optimal in large or urgent cases, but is minimal in normal situations. The level of effectiveness of criminal offence disclosure is largely determined by how strong cross-unit collaboration is built on an ongoing basis. The need for a formal HTCK (Working Procedure Relationship) between Satreskrim and Satintelkam to clarify authorities, responsibilities, and cooperation mechanisms. Increased integrated and cross-functional training to equalise perceptions, increase trust, and reduce sectoral ego. And Polres leaders need to play an active role as mediators and motivators in building open and collaborative communication between units. Establish a permanent cross-unit coordination team facilitated by the Chief of Police and Deputy Chief of Police, to ensure continuity of coordination, not just during major cases. Regular evaluation and monitoring of the quality of coordination, through periodic cross-functional communication forums. And the implementation of a reward and punishment system to increase the commitment of members to the importance of collaboration in disclosing criminal offences.